2018
DOI: 10.24014/sjme.v4i1.5057
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Pemahaman Konsep Matematis dan Kemampuan Pemecahan Masalah Matematis Siswa SMP pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV)

Abstract: Penelitian ini bertujuan untuk mengetahui kemampuan pemahaman konsep matematis dan kemampuan pemecahan masalah matematis siswa pada materi Sistem Persamaan Linear Dua Variabel (SPLDV). Penelitian ini dilaksanakan pada semester genap tahun ajaran 2017/2018 di Pekanbaru. Populasi pada penelitian ini adalah seluruh siswa kelas VIII SMP IT Dar Al-Ma’arif Pekanbaru dengan jumlah sampel sebanyak 28 orang siswa. Instrumen penelitian yang digunakan berupa soal tes kemampuan pemahaman konsep dan kemampuan pemecahan mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
54

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 0 publications
2
23
0
54
Order By: Relevance
“…This was as revealed by Alfiyah (2014) in his research on identifying the metacognition difficulties of students in solving mathematical problems which showed that students' abilities were still low in solving mathematical problems. In line with that, Suraji, Maimunah, & Saragih (2018) argued that the strength of problem-solving and the ability to understand mathematical concepts of students are still relatively low, especially in the application of daily life.…”
Section: Introductionmentioning
confidence: 79%
“…This was as revealed by Alfiyah (2014) in his research on identifying the metacognition difficulties of students in solving mathematical problems which showed that students' abilities were still low in solving mathematical problems. In line with that, Suraji, Maimunah, & Saragih (2018) argued that the strength of problem-solving and the ability to understand mathematical concepts of students are still relatively low, especially in the application of daily life.…”
Section: Introductionmentioning
confidence: 79%
“…Maka dari itu, RMT diharapkan membantu siswa dalam proses belajar untuk memiliki kemampuan memahami materi, berfikir secara tepat dalam membangun konsep sehingga siswa memiliki kemampuan memecahkan masalah dalam pembelajaran matematika (Fitriyani, 2013). Hasil penelitian sebelumnya menunjukkan bahwa Rigorous Mathematical Thinking berpengaruh terhadap pemahaman konsep matematis pada siswa SMP (Hendrayana, 2017;Suraji, MAimunah & Saragih, 2018…”
Section: Pendahuluanunclassified
“…Proof of mathematics is one important component in learning mathematics. Reasoning, mathematical communication, mathematical connections, logical analogies, and algorithms fall into the mathematical proof section which is the most difficult part in mathematics (Suraji, Maimunah, & Saragih, 2018) Mathematical learning is a learning process that requires a lot of high thinking skills. Many cases in the learning outcomes of mathematical proof courses are still very low.…”
Section: Introductionmentioning
confidence: 99%